2013
DOI: 10.1186/1471-2202-14-123
|View full text |Cite
|
Sign up to set email alerts
|

Structural brain abnormalities in cervical dystonia

Abstract: BackgroundIdiopathic cervical dystonia is characterized by involuntary spasms, tremors or jerks. It is not restricted to a disturbance in the basal ganglia system because non-conventional voxel-based MRI morphometry (VBM) and diffusion tensor imaging (DTI) have detected numerous regional changes in the brains of patients.In this study scans of 24 patients with cervical dystonia and 24 age-and sex-matched controls were analysed using VBM, DTI and magnetization transfer imaging (MTI) using a voxel-based approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
80
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(98 citation statements)
references
References 46 publications
15
80
2
1
Order By: Relevance
“…Our cross-sectional observations are partially in agreement with earlier, smaller sized studies concerning VBM in CD that also demonstrated decreased GMV in higher order motor areas, specifically the prefrontal cortex, premotor cortex, and supplementary motor area (Draganski et al, 2003;Pantano et al, 2011;Prell et al, 2013). By contrast, we did not find GMV alterations in the basal ganglia, the cerebellum, or the primary sensorimotor cortex (Draganski et al, 2003;Pantano et al, 2011;Granert et al, 2011).…”
Section: Interpretational Issuessupporting
confidence: 93%
See 2 more Smart Citations
“…Our cross-sectional observations are partially in agreement with earlier, smaller sized studies concerning VBM in CD that also demonstrated decreased GMV in higher order motor areas, specifically the prefrontal cortex, premotor cortex, and supplementary motor area (Draganski et al, 2003;Pantano et al, 2011;Prell et al, 2013). By contrast, we did not find GMV alterations in the basal ganglia, the cerebellum, or the primary sensorimotor cortex (Draganski et al, 2003;Pantano et al, 2011;Granert et al, 2011).…”
Section: Interpretational Issuessupporting
confidence: 93%
“…More specifically, imaging parameters and scanner characteristics influence GM segmentation. Also, the use of newer VBM analysis procedures (see Methods section) and the application of particular statistical methods (correction for non-stationarity of structural images and the use of whole-brain analysis without predefined cortical anatomical regions of interest or masks) may provide an explanation for the discrepancies with these previous, but recent studies (Draganski et al, 2003;Pantano et al, 2011;Prell et al, 2013). Alternatively, differences in population size, age, and disease duration or severity are important for GMV differences.…”
Section: Interpretational Issuesmentioning
confidence: 88%
See 1 more Smart Citation
“…Clinical imaging studies using computed tomography and structural MRI have linked CD with focal lesions of cerebellar circuits (14, 47, 50, 51). A diffusion tensor imaging (DTI) study in individuals with craniocervical dystonia (dystonia of facial and neck muscles combined) indicated abnormal cerebellar microstructure and fiber organization, especially in the anterior cerebellum and vermis (52). Another DTI study showed that persons with CD had decreased axonal fiber organization in the superior cerebellar peduncles, which carry the output fibers from the cerebellum to the thalamus and brainstem (53).…”
Section: Discussionmentioning
confidence: 99%
“…Another DTI study showed that persons with CD had decreased axonal fiber organization in the superior cerebellar peduncles, which carry the output fibers from the cerebellum to the thalamus and brainstem (53). Voxel-based morphometry studies in CD have demonstrated abnormalities in cerebellar gray matter volume, including the anterior cerebellum (15, 17, 52, 54, 55). PET studies have indicated increased glucose metabolism in the cerebellar hemispheres bilaterally (22).…”
Section: Discussionmentioning
confidence: 99%